2022
DOI: 10.3389/fcimb.2022.882608
|View full text |Cite
|
Sign up to set email alerts
|

Peptide of Trichinella spiralis Infective Larval Extract That Harnesses Growth of Human Hepatoma Cells

Abstract: Trichinella spiralis, a tissue-dwelling helminth, causes human trichinellosis through ingestion of undercooked meat containing the parasite’s infective larvae. However, benefits from T. spiralis infection have been documented: reduction of allergic diseases, inhibition of collagen-induced arthritis, delay of type 1 diabetes progression, and suppression of cancer cell proliferation. Since conventional cancer treatments have limited and unreliable efficacies with adverse side effects, novel adjunctive therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Moreover, Ruenchit et al. [68] demonstrated that the extract of T. spiralis‐ infective larvae inhibited the proliferation of human hepatoma, ovarian cancer and lung adenocarcinoma cells. Both larvae and their derived anti‐tumor peptides (identified by proteomics and bioinformatics) showed dose‐dependent detrimental effects against hepatoma cell line (HepG2) [68].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Ruenchit et al. [68] demonstrated that the extract of T. spiralis‐ infective larvae inhibited the proliferation of human hepatoma, ovarian cancer and lung adenocarcinoma cells. Both larvae and their derived anti‐tumor peptides (identified by proteomics and bioinformatics) showed dose‐dependent detrimental effects against hepatoma cell line (HepG2) [68].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [64] and Elhasawy et al [4] found that T. spiralis and its extract had anti-proliferative effect in vitro in the hepatoma cell line (H7402) and in vivo in rats. Moreover, Ruenchit et al [68] demonstrated that the extract of T. spiralis-infective larvae inhibited the proliferation of human hepatoma, ovarian cancer and lung adenocarcinoma cells. Both larvae and their derived anti-tumor peptides (identified by proteomics and bioinformatics) showed dose-dependent detrimental effects against hepatoma cell line (HepG2) [68].…”
Section: Genementioning
confidence: 99%
“…To obtain adult worms, three mice were euthanized by carbon dioxide gas after being infected for seven days. By flushing the digestive tracts with normal saline, adult worms were collected and kept at -80°C ( Ruenchit et al., 2022 ). For larvae preparation, the six infected mice were euthanized by carbon dioxide gas after 2 months of infection.…”
Section: Methodsmentioning
confidence: 99%
“…In silico analysis of anticancer peptides identified three candidates. Antitumor peptide 2 matched the hypothetical protein T01_4238 of T. spiralis and showed a diverse dosedependent effect on the human liver cancer HepG2 cell line, not by causing apoptosis or necrosis but by inducing ROS accumulation, leading to inhibition of cell proliferation [74] .…”
Section: Novel Drug Developmentmentioning
confidence: 99%